Psychoeducational Intervention for Improving Mental Health of Leprosy Patients - Sayang Ajeng Mardhiyah (Shahid Beheshti University of Medical Sciences, 2019)
Leprosy is a chronic disease that can cause disability as a result of nerve damage and causes complex problems. Stigma and association of psychosocial problems tends to occur and increases the risk of mental health disorders of the patients. This research approach is mixing method with AB design type (intervention only). Assessment was conducted by interviewing methods, knowledge tests about leprosy and  instrument Self Reporting Questionnaire-20 (SRQ-20). The sampling technique used purposive sampling, obtained 3 participants and allocated individually. Psychoeducational intervention provided through the description, discussion, sharing, chores and directly exercise through experiential learning approach, which consists of 5 sessions for 90 minutes and delivered every week. The result shown psychoeducational intervention was effective for improving mental health, which marked by the decline of psychological distress symptoms after the intervention. This research suggests the follow-up session of the implementation from the interventions and psychoeducation material can be implemented as routine education in primary health centers for leprosy patients who experience psychological distress.